Personal and situational factors that influence coaches` ability to care - Gano-Overway, L. A.; Magrum, E. D.; McCall, H.; Peterson, M. C. (Journal of Sports Sciences, 2024)
The purpose of this study was to explore how personal and situational factors may influence sport coaches` caring practices. 130 youth sport coaches completed an online survey including perceptions of caring, emotional intelligence, and leadership behaviours. Additionally, coaches were prompted to consider a situation when it was easy or hard to care while also identifying influencing factors. Results revealed coaches` awareness of others` emotions, coaches` ability to use their emotions, and coaches` lower use of autocratic behaviours significantly predicted their perceptions of caring on their teams. Open-ended findings revealed that having a core value/philosophy centred on caring, maintaining a collaborative and welcoming culture, engaging in relationship building, using empathy and listening skills, possessing personal experiences/expertise, encountering advantageous situations, or having positive athlete behaviour made it easier to care. It was more difficult for coaches to care when they experienced poor athlete or parent behaviour, unhelpful situational factors, lack of team culture, differing opinions among staff, or personal factors. These findings provide coaches insight into factors that may influence their ability to care.